2010
DOI: 10.1097/wnp.0b013e3181eaad7d
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal EEGs in Cognitively and Physically Healthy Oldest Old: Findings From The 90+ Study

Abstract: People aged 90 and older (oldest-old), the fastest growing segment of the United States population, are known to have high rates of spells of all types, including strokes, transient ischemic attacks, and seizures. This study examined the prevalence of EEG abnormalities in 12 physically and cognitively healthy oldest-old (mean age=94) with no history of seizures or spells. Abnormalities were found in 83% of participants: temporal intermittent polymorphic slowing was seen in 67%, background slowing (alpha rhythm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…I read with interest the article by Peltz et al (2010) who reported on 12 previously healthy nonagenarians, the majority of whom (10) had diffuse background or focal EEG abnormalities.…”
Section: Eeg In Nonagenariansmentioning
confidence: 96%
“…I read with interest the article by Peltz et al (2010) who reported on 12 previously healthy nonagenarians, the majority of whom (10) had diffuse background or focal EEG abnormalities.…”
Section: Eeg In Nonagenariansmentioning
confidence: 96%
“…Increased fast activity, diffuse slowing, and focal disturbances [115,116] Healthy Controls (HC) versus MCI Increasing alpha power, enhanced alpha coherence, objective and working memory disturbances distinguish cortical processing of MCI and controls during memory activities. [114,118,119] Theta/Alpha Ratio study younger adults differentially recruited disparate neural regions and frequency bands than older adults with MCI in response to task engagement. higher theta power with relative decrease in alpha power in the study phase in medial/temporal channels by older adults [120] HC , MCI without DM, MCI with DM Peak power frequency of alpha 2 is higher, with significantly higher hippocampal atrophy and alpha-2/alpha-1 power ratio among MCI with DM, than MCI without DM and HC groups [128] Differentiating frontotemporal dementia (FTD) from Alzheimer's disease (AD) HC α-generators are in the posterior regions of the brain.…”
Section: Normal Agingmentioning
confidence: 99%
“…Studies using EEG signals and neuroimaging have correlated their activity and the parietal lobes with different kinds of cognitive information processing (memory, language, concept retrieval and music processing) [113,114]. Table The lateral prefrontal cortex, mediotemporal areas, posterior association cortex, temporal lobe, hippocampus, and parietal lobe are functionally involved with memory in general and working memory, which is responsible for information encoding, maintenance and decoding [114]. Thus age related changes in these areas would result in changes in brain wave oscillations and coherence [114].…”
Section: Alpha Waves and Cognitive Impairments In Normal Aging And Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Clear changes in the alpha rhythm are seen as the human brain ages, including AF slowing, reduction in alpha power, and a shift in the posterior-to-anterior direction. 5 12 13 14 15 16 17 18 19 20 21 22 Slowing of the EEG has also been found to indicate CNS pathology, in particular slowing of AF has been observed repeatedly in patients with dementia. 23 24 25 26 27 28 29 30 31 32 33 34…”
Section: Introductionmentioning
confidence: 99%